Efficacy and Tolerability of Amlodipine for Patients with Hypertension - Warda Mehboob, Hadia Akhtar, Kinza Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: For dealing with mild to moderate hypertension, Current hypertension recommendations recommend initial low-dose antihypertensive monotherapy. Objectives: The main objective of this study is to find out if amlodipine is effective and safe for people with high blood pressure. Material and methods: This cross-sectional research was done in Midcity hospital, Jail road Lahore between January 2021 to November 2021. The data was acquired by a non-probability consecutive sampling approach. Results: The data was collected from 100 patients, genders equally. The average systolic and diastolic benefits are presented in Table 1, broken down by age and gender. The average systolic blood pressure was 124.2 15.0 mmHg, while the average diastolic blood pressure was 83.4 9.5 mmHg. Systolic and diastolic blood pressures increased at a rate that was greatest in the oldest age group of males studied. Conclusion: It is concluded that Amlodipine reduces ambulatory blood pressure with the same tolerance as a low-dose first treatment. This strategy may be helpful in the treatment of blood pressure and, if implemented extensively in clinical practise, should result in an improvement in the percentage of patients whose hypertension is under control.